Analisis Gaya Kepemimpinan dan Kerja Tim terhadap Kinerja Karyawan di Bank Sumsel Babel Kapten A. Rivai Palembang - Raisah Filzah Ibrahim; Purwati Purwati; Neneng Miskiyah (International Forum of Researchers and Lecturers, 2025)
The purpose of this study is to examine the extent to which the relationship between leadership style and teamwork influences the work results of employees of Bank Sumsel Babel, Kapten A. Rivai Branch, Palembang. This study uses a quantitative approach with a population and sample of 59 people determined through a saturated sampling method, so that the entire population becomes research respondents. Research data were obtained from two sources, namely primary data through the distribution of questionnaires to employees, and secondary data that supports the results of data processing. Data analysis was carried out comprehensively by including testing classical assumptions to ensure model validity, testing the feasibility of research instruments, calculating the coefficient of determination, and applying multiple regression analysis tested through the F test and t test. The results of the study indicate that leadership style and teamwork have a positive and significant influence on employee performance, both partially and simultaneously. This finding shows that effective leadership and solid teamwork can increase employee productivity and work quality. The large contribution of both independent variables to employee performance is indicated by the coefficient of determination value of 66.2%, which means that more than half of the variation in employee performance can be explained by leadership style and teamwork. Meanwhile, the remaining 33.8% is influenced by factors outside this study, such as the work environment, individual motivation, and organizational reward systems. This study emphasizes the importance of appropriate leadership and synergy among team members in building optimal employee performance. The practical implication of these findings is the need for management to continuously improve leadership quality and encourage better teamwork in the banking workplace.